The development of the mollusc fauna in the Cenomanian of the stratigraphic sequence of Visogliano (Karst of Trieste, Italy) - Caffau, Mauro; Pugliese, Nevio; Pleničar, Mario (Geologija, 1994)
The stratigraphic sequence of Visogliano (Karst of Trieste) belongs to lower part of the Zolla Member of the still informal and provisional “Trieste Karst Limestone Formation” and has been attributed to Middle-Late Cenomanian. This sequence records an environmental evolution of more or less restricted settings, where a rich mollusc fauna is present. Among the molluscs, six radiolitid species occur (Radiolites carsicus n. sp., Radiolites peroni, Praeradiolites acutilamellosus n. sp., Praeradiolites cf. P. fleuriausus, Sauvagesia sharpei, and Durania acuticostata n. sp.). Of these, three species are described as new (Radiolites carsicus n. sp., Praeradiolites acutilamellosus n. sp., and Durania acuticostata n. sp.). In addition, attention has been focussed on the link between radiolitids and environmental changes to refine the previously described environmental evolution. In this regard, a hierarchy of tolerability to environmental changes can be also suggested. The most tolerant radiolitids species are Praeradiolites cf. P. fleuriausus and Sauvagesia sharpei, meanwhile the least tolerant ones are Radiolites carsicus n. sp., Radiolites peroni, Praeradiolites acutilamellosus n. sp., and Durania acuticostata.